Is there a wage penalty associated with degree of indecision in career aspirations? Evidence from the BCS70 - Ricardo Sabates; Leslie Morrison Gutman; Ingrid Schoon (Longitudinal and Life Course Studies, 2017)
In this longitudinal study, we test whether varying degrees of indecision about future career choices at age 16 have long-term economic consequences in adulthood, taking into account potential gender differences. Findings from a British cohort born in 1970 indicate that young people who were completely undecided about their job choices did experience a wage penalty at age 34 compared to young people who were certain about their job aspirations. This association was significant even after controlling for family socioeconomic status, parental expectations and academic ability at age 16. However, the wage penalty was mediated by educational attainment and part-time employment at age 34. Not being entirely certain about one's future profession by age 16 seems to be part of a career decision making process which does not necessarily incur a wage penalty for most young people, especially if it involves the acquisition of education qualifications.
Keywords: 330; career indecision; career aspirations; earnings; 1970 British Cohort; Britain